Case report: Mechanical thrombectomy for acute basilar artery occlusion via persistent hypoglossal artery - Zhang, Xin; Wang, Jiaxiong; Cao, Zhipeng; Liu, Yingtao; Dong, Yi; Cheng, Xin; Gao, Chao; Gu, Yuxiang (Frontiers in Neurology, 2023)
The persistent hypoglossal artery (PHA) is a rare carotid-vertebrobasilar anastomosis in adults. Here, we report a case of mechanical thrombectomy for acute basilar artery occlusion via the PHA. A 44year-old man was admitted to our stroke unit with an unstable gait and aphasia for 2 hours. The baseline National Institutes of Health Stroke Scale (NIHSS) score was 4, but the clinical symptoms continued to worsen. Computed tomography angiography showed the absence of the basilar artery and an abnormal anastomosis between the anterior and posterior circulation. Clinical symptoms continued to worsen, and endovascular treatment was scheduled. The PHA was demonstrated and basilar artery occlusion confirmed using digital subtraction angiography. Mechanical thrombectomy with a stent retriever and aspiration was performed via the PHA, and modified thrombolysis at cerebral infarction level 3 was achieved. The patient underwent intra-venous antiplatelet therapy after the operation, and follow-up neuroimaging revealed multiple small infarcts in the cerebellum and medulla oblongata. The patient was discharged after 10 days for further rehabilitation, with an NIHSS score of 25. At 10 months follow-up, the NIHSS score decreased to 18. Recognition of this rare variation is particularly important for interventional strategy determination and rapid recanalization of basilar artery occlusion.